Clinical and Electrophysiological Outcome Measures of Patients With Post-Infectious Neurological Syndromes Related to COVID-19 Treated With Intensive Neurorehabilitation - Avenali, Micol; Martinelli, Daniele; Todisco, Massimiliano; Canavero, Isabella; Valentino, Francesca; Micieli, Giuseppe; Alfonsi, Enrico; Tassorelli, Cristina; Cosentino, Giuseppe (Frontiers in Neurology, 2021)
Background: The clinical spectrum of coronavirus disease 2019 (COVID-19), due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, may be quite wide, including neurological symptoms. Among them, para-infectious or post-infectious neurological syndromes (PINS), caused by an inflammatory response against the central and/or peripheral nervous system, have been reported. The aim of this paper is to illustrate the functional and neurophysiological recovery in a series of subjects with COVID-19-related PINS who underwent intensive neurorehabilitation. Materials and Methods: Five patients with PINS associated with COVID-19 were evaluated at baseline and followed up for 6 months. Three of them had polyradiculoneuropathy and two patients had myelitis. The onset of the neurological syndromes was temporally associated with the SARS-CoV-2 infection. After completing the acute neurological treatments in the intensive care unit, patients underwent a personalized multidisciplinary rehabilitation program. An in-depth clinical, functional, and electrophysiological assessment was carried out at baseline and at 3- and 6-month follow-ups. Results: Among patients with polyradiculoneuropathy, the electrophysiological evaluation at baseline disclosed an acute inflammatory demyelinating polyradiculoneuropathy (AIDP) in two patients and an acute motor and sensory axonal neuropathy (AMSAN) in the third patient. At follow-up, the electrophysiological features improved in one subject with AIDP and were stable in the remaining two cases. The functional assessment after neurorehabilitation showed global recovery and full independence in walking and in activities of daily life in one patient and mild improvement in the other two cases. Of the two subjects with myelitis, the baseline electrophysiological examination showed a prolonged central motor conduction time, which returned to normal in one patient, whereas it improved but remained pathological in the other patient at follow-up. The neurorehabilitation led to a substantial functional improvement in both subjects. Discussion and Conclusions: This is the first study to describe clinical and electrophysiological aspects along with medium-term outcome in patients with COVID-19-related neurological manifestations who underwent an intensive rehabilitation program. The functional outcome following neurorehabilitation in patients with PINS related to SARS-CoV-2 infection is variable. In our small case series, subjects with polyradiculoneuropathy had a poorer recovery compared to patients with myelitis. The clinical course largely paralleled the follow-up electrophysiological findings.